Análise morfológica de isoformas de miosina não muscular tipo II em carcinoma epidermóide - Dias, Otávio Francisco Gomes (2012)
Cell migration is a prominent feature in cancer metastasis and the characterization of proteins related to migration is important in order to understand the behavior of tumor cells and their invasiveness during tumor progression. Among the proteins involved in cell migration, isoforms of non-muscle myosin type II play a pivotal role in several events related to cell migration, such as contractility, adhesion and cellular signaling. There are three isoforms of myosin type II that can be expressed in mammalian cells: myosin IIA (MIIA), myosin IIB (MIIB) and myosin IIC (MIIC). However, few studies have been conducted to characterize the expression and distribution patterns in cells of different types of tumors, including oral squamous cell carcinoma. The aim of the study was to analyze the expression and distribution of isoforms of myosin II (A, B and C) in surgical fragments of squamous cell carcinoma. Fragments of surgical specimen were collected from different regions of the tumor: a tumor-free zone, the center of the tumor and the invasion zone. These samples (n = 4) were fixed, crioprotected, cut on criostat, submitted to immunolocalization of MIIA, MIIB and MIIC and analyzed on confocal microscopy. The three isoforms of myosin II were expressed differently and showed distinct distribution in accordance with the region of the tumor sample. MIIA and MIIC were overexpressed at the center zone when compared with the free zone, whereas strong staining revealed MIIB at the zone invasion. Based on these observations, the isoforms of myosin IIC and IIA appeared to be more associated with tumor proliferation while MIIB appeared to be more involved in the invasive behavior of tumor, indicating that the isoforms can participate in different ways regulating the behavior and development of tumor type analyzed.